Diagnostic Value and Safety of Emergency Single-Balloon Enteroscopy for Obscure Gastrointestinal Bleeding - Yipin Liu; Weiwei Jiang; Guoxun Chen; Yanqing Li (Gastroenterology Research and Practice)
Background. This study assesses the diagnostic performance of emergency single-balloon enteroscopy (SBE) for obscure gastrointestinal bleeding (OGIB) under general anesthesia versus conscious sedation. Study. The data of 102 OGIB in-patients from June 2015 to June 2018 were retrospectively analyzed. The diagnosis and detection rates and adverse events were calculated overall and in relation to age, gender, type of operation and anesthesia, bleeding type, different times of examination, and SBE route. All statistical analyses were performed using SPSS 24.0, and the diagnosis and detection rates were compared using the Chi-square test. Results. Among the 102 patients, 66 patients had positive findings, while 11 patients had suspected positive findings, and the diagnosis and detection rates were 64.7% and 75.5%, respectively. Ulcers (19.6%) and tumors (16.7%) were the most common causes of OGIB. There were no statistical differences in diagnosis and detection rates between the ages of ≥60 and <60 and between different genders. Patients with emergency SBE had higher diagnosis and detection rates (68.6% vs. 35.3%, P=0.023; 80.0% vs. 47.1%, P=0.016, respectively), when compared with nonemergency SBE patients. The diagnosis rate at 24 hours was higher than that at 2-7 days and one week (88.0% vs. 61.5%, P=0.030; 88.0% vs. 53.8%, P=0.007). For overt bleeding, the difference in diagnosis rates at 24 hours, 2-7 days, and one week was statistically significant (100.0% vs. 57.1%, P=0.006; 100.0% vs. 57.1%, P=0.006). For occult bleeding, the pairwise comparison revealed no statistical difference. Patients with general anesthesia had a higher detection rate, when compared to patients with conscious sedation (87.9% vs. 63.9%, P=0.004). In addition, adverse events under general anesthesia were lower, when compared to adverse events under conscious sedation (28.8% vs. 69.4%, P=0.020). There was no significant difference in adverse events at the different time points (P>0.05). Conclusion. Emergency SBE under general anesthesia achieves higher diagnosis and detection rates, and fewer adverse events under conscious sedation, when compared to nonemergency SBE, regardless of the route. For patients with overt bleeding, it is easier to find lesions by emergency SBE within 24 hours.